Replication of annulus fibrosus through fabrication and characterization of polyurethane and cellulose nanocrystal composite scaffolds. Issue 1 (2nd January 2019) - Frost, Brody A.; Foster, E. Johan
Abstract: This study sought to obtain a simple scaffold for annulus fibrosus (AF) repair or replacement using a combination of polyurethane (PU) reinforced with cellulose nanocrystals (CNCs). Composites containing up to 20 wt% CNCs were solvent casted and fabricated into ribbons and radially layered structures to be mechanically tested in tension, compression, creep, and relaxation. Tension and compression testing on swollen composite films and ringed structures, respectively, revealed that the PU 90/10 and PU 80/20 composites had elastic moduli most closely related to the natural AF tissues. Creep and relaxation revealed that the composite materials show a greater percentage of elastic response and longer relaxation times than natural intervertebral disc (IVD) tissues. It was shown that this approach leads to a scaffold that nearly mimics the mechanical properties of natural IVD tissues, while allowing fine tuning of these mechanical properties by varying CNC content and the ringed structure. Graphical Abstract: